Massive pericardial effusion as the first manifestation of childhood non‐Hodgkin's lymphoma: A case report - Behzad Alizadeh (Wiley, 2021)
Abstract Although one of the serious manifestations of advanced malignancies is pericardial involvement, pericardial involvement of lymphoma is extremely rare. We present a case of a 6‐year‐old girl arriving at the hospital with dyspnea and pleuritic chest pain, which is eventually diagnosed with massive pericardial effusion due to mediastinal non‐Hodgkin lymphoma.